PERAN PSIKOLOGI SOSIAL DALAM MENANGANI PRASANGKA BURUK TERHADAP KASUS SATPAM MEMUKUL ANJING - Tyo Hendryan; Sulistiasih (ADISAM PUBLISHER, 2024)
This research aims to determine the role of social psychology in dealing with negative prejudice directed at someone, as well as finding out how this prejudice can occur through chronology and clarification from the victim. The case that occurred on June 6 2024 was regarding a Plaza Indonesia security guard who beat a dog which turned out to be a misunderstanding due to lack of information from the author and the public. Social psychology plays a role in this case, in helping the victim overcome the misunderstandings and dismissal they experienced as well as providing education to the public not to be prejudiced and spread misinformation widely.